Emanuel : studies in Hebrew Bible, Septuagint, and Dead Sea scrolls in honor of Emanuel Tov - Tov, Emanuel.; Paul, Shalom M.; Ben-David, Eva. (Vetus Testamentum, Supplements, 2003)
This volume honors the lifetime of scholarly contribution and leadership of Professor Emanuel Tov, Judah L. Magnes professor of Bible at the Department of Bible, the Hebrew University of Jerusalem. Colleagues from all over the world have contributed significant studies in the three areas of Tov's primary interest and expertise: the Hebrew Bible, its Greek translations, and the Dead Sea Scrolls. This Festschrift is a fitting tribute to one of the generation's leading scholars, whose dedicated efforts as editor-in-chief have brought about the complete publication of the Dead Sea Scrolls.